2002
DOI: 10.1091/mbc.01-11-0553
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p42 Mitogen-activated Protein Kinase (MAPK), but not c-Jun NH2-Terminal Kinase, Induces Phosphorylation and Stabilization of MAPK PhosphataseXCL100 inXenopusOocytes

Abstract: Dual-specificity protein phosphatases are implicated in the direct down-regulation of mitogenactivated protein kinase (MAPK) activity in vivo. Accumulating evidence suggests that these phosphatases are components of negative feedback loops that restore MAPK activity to low levels after diverse physiological responses. Limited information exists, however, regarding their posttranscriptional regulation. We cloned two Xenopus homologs of the mammalian dual-specificity MAPK phosphatases MKP-1/CL100 and found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 92 publications
3
29
0
Order By: Relevance
“…7), possibly via phosphorylation by ERK or other protein kinases. Recently, threonine 168 has been identified as a third phosphorylation site targeted by ERK (37). Whether threonine 168 plays a role in LPS-stimulated MKP-1 stabilization remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…7), possibly via phosphorylation by ERK or other protein kinases. Recently, threonine 168 has been identified as a third phosphorylation site targeted by ERK (37). Whether threonine 168 plays a role in LPS-stimulated MKP-1 stabilization remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Xenopus CL100 (XCL100), a homologue of human MKP-1, is phosphorylated by ERK in a cell cycle-dependent manner. In the case of XCL100, serine residue(s) were phosphorylated during the G 2 phase, and serine and threonine residues were phosphorylated during M-phase (53). Although the biological consequence of MKP-7 phosphorylation is currently unknown, it is important that Ser-446 in the CTS is a phosphorylation site.…”
Section: Discussionmentioning
confidence: 99%
“…6A, serine-phosphorylated MKP1 expression was increased in HSP25 or HSP70i overexpressed cells, and interaction between HSP25 or HSP70i and MKP1 was also increased. Transient transfection of site-directed mutants of Mkp1 on cysteine 258 to serine (Mkp1-C258S), which abolished phosphatase activity of MKP1 (23), revealed that expressions of HSP25, HSP70i, and HSF1 were reduced by Mkp1-C258S transfection, and phosphorylations of both HSF1 and ERK1/2 by HSP25 or HSP70i were restored by this mutant (Fig. 6B), even though mutation of Mkp1 on cysteine 258 did not affect the binding activity with HSP25 or HSP70i (data not shown).…”
Section: Mutant Forms Of Hsf1 Abolished the Enhanced Expression Of Hsmentioning
confidence: 99%